The Hidden Dangers: How Synthetic Organic Compounds Impact Health and the Environment - Jha, Ashima; Jha, Meena (International Journal of Nursing Information, 2024)
Human health care and environmental preservation are two interconnected aspects of modern life. Synthetic organic compounds have significantly contributed to various industries, including agriculture and cosmetics, offering notable benefits. However, these compounds also pose risks to human health and environmental sustainability. This study aims to review synthetic organic compounds from multiple perspectives, comprehensively understanding their toxicological impacts and focusing on their potential risks to human health and the environment while exploring safer alternatives and mitigation strategies. A literature review approach was employed by sourcing primary articles using keywords related to synthetic organic compounds and their impacts. Databases such as PubMed, Google Scholar, ResearchGate, and Elsevier were utilized, alongside more than 50 secondary sources, for in-depth analysis. The findings highlight the potential adverse effects of exposure to these compounds and evaluate existing regulatory measures, underscoring the urgent need for enhanced strategies to mitigate associated risks. By emphasizing the principles of green chemistry, this review advocates for sustainable practices to reduce long-term contamination, thus protecting human health and the environment. This study contributes to nursing and health science by raising awareness about toxic exposures to synthetic compounds daily and offers valuable insights to inform policy frameworks and practical interventions. These insights aim to minimize health risks while supporting nurses’ roles in health promotion and disease prevention, enhancing their capacity to effectively address environmental and chemical health concerns.